2022
DOI: 10.3389/fbioe.2022.975840
|View full text |Cite
|
Sign up to set email alerts
|

Involvement of PI3K/Akt signaling pathway in promoting osteogenesis on titanium implant surfaces modified with novel non-thermal atmospheric plasma

Abstract: Non-thermal atmospheric plasma (NTAP) modification to induce a hydrophilic titanium (Ti) surface with less carbon contamination, has been demonstrated to boost the osteogenic responses. In this study, we investigated the underlying bone formation mechanism of NTAP-Ti, and the involvement of PI3K/Akt signaling pathway in regulating osteogenic activities on NTAP-Ti surfaces. NTAP was employed for Ti activation, and PI3K inhibitor, LY294002, was applied to the suppression of PI3K/Akt pathway. We systematically an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 48 publications
0
6
0
1
Order By: Relevance
“…Ghosh Choudhury et al demonstrated that BMP-2 invokes osteoblast differentiation by means of activating the PI3k/AKT pathway [ 26 ]. LY294002 is a commonly used pharmacological inhibitor that has been widely used to inhibit PI3K signaling [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…Ghosh Choudhury et al demonstrated that BMP-2 invokes osteoblast differentiation by means of activating the PI3k/AKT pathway [ 26 ]. LY294002 is a commonly used pharmacological inhibitor that has been widely used to inhibit PI3K signaling [ 27 ].…”
Section: Introductionmentioning
confidence: 99%
“…33 In addition, previous studies showed that NTAP-treated implants promoted the biological behavior of rat bone marrow mesenchymal stem cells (BMSCs) and MC3T3-E1. 34,35 Previous comparative experiments also revealed that the osteogenic effect of the NTAP-treated implant was similar to that of the Straumann SLActive implant. 36 In summary, the NTAP device boasts highly efficient, convenient, and biologically safe advantages.…”
Section: Introductionmentioning
confidence: 83%
“…In accordance with our findings, Ren et al observed the activation of the PI3K/AKT signaling pathway in the melatonin-induced preservation of the osteogenic potential of MC3T3-E1 preosteoblast cells against iron overload [ 40 ]. Conversely, the inhibition of PI3K phosphorylation by LY294002 hindered the osteointegration of titanium implant surfaces treated with innovative non-thermal atmospheric plasma, leading to a decline in osteoblast proliferation and differentiation [ 41 ]. The participation of the PI3K/AKT pathway has been previously validated in a study where the inhibition of PI3K resulted in the elimination of the bone regenerative impact of nano-laponite hydrogel, as demonstrated by the attenuation of calcified matrix formation.…”
Section: Discussionmentioning
confidence: 99%